2018
DOI: 10.1002/smj.2764
|View full text |Cite
|
Sign up to set email alerts
|

Scale matters:The scale of environmental issues in corporate collective actions

Abstract: Research Summary: Much of the research on corporate collective action to manage common pool resources is focused on coordinated actions, such as voluntary programs, rather than collaborative actions, such as technology sharing. In this article, we examine inductively the collective actions taken by a consortium of 12 oil sands companies to address three environmental issues of different scale. We identified a set of organizing rules that determined whether the relationship among industry members would be colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 92 publications
0
78
0
Order By: Relevance
“…Albareda et al 2007). For ecological sustainability, previous research has shown that regulation is an important determinant (Christmann 2004;Eberlein and Matten 2009), as is industry self-regulation (Bowen et al 2018;Hoffman and Georg 2013), depending on the respective industry. Based on our case, we found that both regulation and self-regulation were included as strong influences on internal elements of the public-private partnership.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Albareda et al 2007). For ecological sustainability, previous research has shown that regulation is an important determinant (Christmann 2004;Eberlein and Matten 2009), as is industry self-regulation (Bowen et al 2018;Hoffman and Georg 2013), depending on the respective industry. Based on our case, we found that both regulation and self-regulation were included as strong influences on internal elements of the public-private partnership.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to or in replacement of regulation, private actors are often found to establish industry self-regulation. Industry self-regulation is used as an umbrella term for initiatives, often led by industry associations, to establish rules and standards to regulate corporate behaviour and competition, while industry members decide independently about their participation and extent of commitment (Barnett and King 2008;Bowen et al 2018;Grabosky 2013;Hart 2010;Hoffman and Georg 2013). Industry self-regulation can generally be proactive or reactive and is expected to complement regulation (Gupta and Lad 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies that take an explicit interest in coopetition for sustainability do discuss different types of outcomes on a general level (Bowen, Bansal, & Slawinski, 2018;Christ et al, 2017;Limoubpratum et al, 2015;Meehan & Bryde, 2015;Peloza & Falkenberg, 2009;Planko, Chappin, Cramer, & Hekkert, 2019;Stadtler, 2017;Volschenk et al, 2016). Still, there is a lack of a systematic unpacking of what these possible outcomes of coopetition for sustainability may actually be.…”
Section: Coopetition and Sustainable Developmentmentioning
confidence: 99%
“…Yet many forms of social entrepreneurship involve collective organizing efforts that depend on voluntary participation rather than formal employment and that pursue a triple rather than double bottom line. Examples include community transformation initiatives in the developing world (Haugh and Talwar 2016;Pless and Appel 2012), sustainability alliances (Bowen et al 2018), and cross-sector partnerships (Nicholls and Huybrechts 2016;Sharma and Bansal 2017). Indeed, some scholars have argued that collaborative partnerships are required to produce effective solutions to large-scale social problems (Sud et al 2009).…”
Section: Introductionmentioning
confidence: 99%